Comparative study on the removal of different-type organic pollutants on hierarchical tetragonal bismutite microspheres: Adsorption, degradation and mechanism. (1st January 2020) - Xu, Ruibing; Su, Minhua; Liu, Yonghui; Chen, Zibiao; Ji, Cheng; Yang, Minling; Chang, Xiangyang; Chen, Diyun
Abstract: By selecting three typical dyes with different charge properties as model pollutants, the inherent roles of adsorption, degradation pathways and mechanism of using bismutite (Bi2 O2 CO3 ) photocatalyst to remove organic pollutants from aqueous solution were systematically studied. Bismutite can effectively degrade dyestuffs [e.g., anionic dye methyl orange (MO), amphoteric dye rhodamine B (RhB), cationic dye methylene blue (MB), and their mixed solutions]. Degradation kinetics are diverse when treating different types of dyes, which is possibly because of their significantly different adsorption behavior on bismutite. The inherent molecular structure, charge properties of dyes, and attraction between dye and bismutite may particularly dominate degradation efficiency. Moreover, h + and · O2 − were main active species for MO and RhB degradation, whereas rich adsorption of MB on bismutite significantly inhibited the separation of electron-hole pairs and thus · OH was dominant for MB degradation. According to the intermediates generated during the reaction, the degradation pathways of three dyes were proposed. This study revealed the adsorption and photocatalytic behavior of different-type dyes on the tetragonal bismutite catalyst, which facilitates in understanding the degradation processes and mechanism of different-type organic pollutants and promotes the practical application of bismutite in complex wastewater purification. Graphical abstract: Image 1 Highlights: The molecular structure and charge properties of dyes significantly affected the removal of dyes by bismutite. h + and · O2 − were dominantly active species for MO and RhB degradation. Rich adsorption of MB on bismutite significantly inhibited the separation of electron-hole pairs. Multi-analytical methods were used to study degradation pathways and mechanism.